2021
DOI: 10.1111/asj.13581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese wolfberry and astragalus extracts on growth performance, pork quality, and unsaturated fatty acid metabolism regulation in Tibetan fragrant pigs

Abstract: We studied the effects of wolfberry and astragalus extract on the growth performance, carcass traits, and meat quality of Tibetan fragrant pigs, and we want to explain the mechanism of the difference from the level of RNA Seq. Twelve healthy 120-day-old Tibetan fragrant pigs weighing 35 AE 2 kg were divided randomly into two groups, each with six pigs. The control group was fed a basal diet, and the wolfberry and astragalus extract (WAE) group was fed a basal diet +1‰ of WAE. The experimental period was 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…This is evidenced by the decrease in both the serum Glu and TG levels of ZQ-1 g group at 62 d. Those mentioned above suggested that the fat deposition was the main factor of growth promotion of ZQ on finishing pigs. Similar results have been reported in other previous research, the dietary supplementation of Chinese wolfberry and astragalus extracts could improve the growth performance and intervene in key genes related to fatty acid metabolism in Tibetan fragrant pigs [ 63 ]. In the review article by Cui et al, they summarized the intramuscular fat deposition-promoting effect of Chinese herbal medicines (CHMs), which contain multiple active ingredients, such as polyphenols, flavonoids, polysaccharides [ 64 ].…”
Section: Discussionsupporting
confidence: 90%
“…This is evidenced by the decrease in both the serum Glu and TG levels of ZQ-1 g group at 62 d. Those mentioned above suggested that the fat deposition was the main factor of growth promotion of ZQ on finishing pigs. Similar results have been reported in other previous research, the dietary supplementation of Chinese wolfberry and astragalus extracts could improve the growth performance and intervene in key genes related to fatty acid metabolism in Tibetan fragrant pigs [ 63 ]. In the review article by Cui et al, they summarized the intramuscular fat deposition-promoting effect of Chinese herbal medicines (CHMs), which contain multiple active ingredients, such as polyphenols, flavonoids, polysaccharides [ 64 ].…”
Section: Discussionsupporting
confidence: 90%
“…Intestinal microorganisms not only provide energy for life-sustaining activities, but are also involved in regulating lipid storage ( Backhed et al, 2004 ). Additionally, the abundance of intestinal microflora is significantly correlated with obesity parameters ( Bergamaschi et al, 2020 ; Hao et al, 2021 ). Colonic microbes and complex traits such as obesity have been shown to be closely related ( Backhed et al, 2004 ; Camarinha-Silva et al, 2017 ) in humans, mice, and other animals.…”
Section: Discussionmentioning
confidence: 99%
“…Menchetti [ 29 ] found that the addition of 1% goji berries to rabbit diets led to a significant increase in final body weight and feed efficiency, a decrease in mortality, and an improvement in reproductive performance. Hao et al [ 30 ] discovered that supplementing feed with 1% wolfberry and astragalus extracts significantly improved the growth performance of fattening pigs. Furthermore, it regulated the unsaturated fatty acid content of pork, thereby improving its nutritional value.…”
Section: Discussionmentioning
confidence: 99%